To use the distributive property (also known as the FOIL method for binomials), we need to multiply each term in the first binomial by each term in the second binomial.
Given the expression \((x + 8)(x - 2)\):
-
First: Multiply the first terms:
\(x \cdot x = x^2\) -
Outer: Multiply the outer terms:
\(x \cdot (-2) = -2x\) -
Inner: Multiply the inner terms:
\(8 \cdot x = 8x\) -
Last: Multiply the last terms:
\(8 \cdot (-2) = -16\)
Now, let's combine these results:
\[ x^2 - 2x + 8x - 16 \]
Combine like terms (-2x and 8x):
\[ x^2 + 6x - 16 \]
So, the polynomial \((x + 8)(x - 2)\) can be rewritten as:
\[ x^2 + 6x - 16 \]
Therefore, the completed blanks are:
- __z^2 = 1 (coefficient of \(x^2\))
- __x = 6 (coefficient of \(x\))
- __ = -16 (constant term)
Thus, the final result is: 1 for \(z^2\), 6 for \(x\), and -16 for the constant.